2004
DOI: 10.1248/jhs.50.17
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Emamectin, its Metabolites, Milbemectin, Ivermectin and Abamectin in Tomato, Japanese Radish and Tea by LC/MS

Abstract: We developed a simple and rapid analytical method for determining the residues of emamectin benzoate, milbemectin, abamectin, ivermectin and emamectin metabolites in tomato, Japanese Radish and Japanese tea by liquid chromatography/mass spectrometer (LC/MS) with electrospray ionization (ESI). A sample extracted with acetone was simply cleaned up using only a Sep-Pak C18, and then directly measured by LC/MS (ESI). Several LC/ MS measurement conditions were studied that included the mobile phase, solvent for sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The present study also indicates that the residues of emamectin benzoate on tomatoes were rapidly decreased. These results are supported by Yoshii, et al, (2001Yoshii, et al, ( & 2004 who determined the residues of emamectin and its metabolites, in tomato and Japanese radish by liquid chromatography, and found that emamectin rapidly degraded to its metabolites.…”
Section: Residues Of Fenazaquinsupporting
confidence: 53%
See 2 more Smart Citations
“…The present study also indicates that the residues of emamectin benzoate on tomatoes were rapidly decreased. These results are supported by Yoshii, et al, (2001Yoshii, et al, ( & 2004 who determined the residues of emamectin and its metabolites, in tomato and Japanese radish by liquid chromatography, and found that emamectin rapidly degraded to its metabolites.…”
Section: Residues Of Fenazaquinsupporting
confidence: 53%
“…Emamectin benzoate is semi-synthetic derivative from abamectin (Prabhu, et al, 1991). It is registered as an acaricide for different food commodities in different countries (Yoshii, et al, 2004).…”
Section: Residues Of Emamectin Benzoatementioning
confidence: 99%
See 1 more Smart Citation
“…Because of its high toxicity to agricultural pests abamectin is widely used to control insects and mites in tea, vegetables, and fruits [3]. Abamectin present in various biological matrices including animal tissues, serum, fruits, and vegetables can be successfully determined by high-performance liquid chromatography (HPLC) in the reverse phase mode, coupled with different detectors, namely, ultraviolet detection (UVD), fluorescence detection (FLD), and mass spectrometry (MS) [3][4][5]. However, there is no report in the literature on the methodology for the determination of abamectin residues present in tea.…”
Section: Introductionmentioning
confidence: 99%
“…The low stability of the derivatized samples led to a decrease in the reproducibility of the result, and derivatization reagents produced by‐products that can reduce the lifetime of the chromatographic column. On the other hand, MS) was able to detect avermectins in environmental and food samples with high sensitivity and without derivatization .…”
Section: Introductionmentioning
confidence: 99%